Are changes in HSPA1A, HSPB1 and LDHb genes expression during physical performance "till exhaustion" independent of their exercise possibility? - Jastrzebski Zbigniew; Zychowska Malgorzata (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2014)
Background: The aim of the study was to designate changes in the expression of HSPA1A, HSPB1 and LDHb in elite rowers after completing a test "till exhaustion" on a rowing ergometer. Finally, we searched for the answer whether there are significant correlations between the expression of the genes and anaerobic threshold (AnT) or the maximal oxygen uptake (VO2max).